2000
DOI: 10.1161/01.str.31.6.1393
|View full text |Cite
|
Sign up to set email alerts
|

Mild and Moderate Hypothermia (α-Stat) Do Not Impair the Coupling Between Local Cerebral Blood Flow and Metabolism in Rats

Abstract: Background and Purpose-The effects of hypothermia on global cerebral blood flow (CBF) and glucose utilization (CGU) have been extensively studied, but less information exists on a local cerebral level. We investigated the effects of normothermic and hypothermic anesthesia on local CBF (LCBF) and local CGU (LCGU). Methods-Thirty-six rats were anesthetized with isoflurane (1 MAC) and artificially ventilated to maintain normal PaCO 2 (␣-stat). Pericranial temperature was maintained normothermic (37.5°C, nϭ12) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
1

Year Published

2002
2002
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 42 publications
2
26
1
Order By: Relevance
“…Dudley and colleagues (Dudley et al, 1982) reported that a 60mg/kg single dose of α-chloralose reduces the cerebral glucose utilization rate to 35−47% of that in the awake preparation in the cortex, and Nakao et al (2001) found thata 50mg/kg bolus followed by a 40 mg/kg/h maintenance dose reduced glucose utilization to 36% in the sensory motor cortex. These reductions in cerebral glucose metabolism in the cortex are very similar to the reductions observed with isoflurane at the concentrations used in the present study (Krafft et al, 2000;Ori et al, 1986). In addition, the α-chloralose dosing used (60 mg/kg bolus; 30 mg/kg/hr maintenance) is in line with the average dosing used in a variety of functional activation studies (64±15 mg/kg; 34±10 mg/kg/hr).…”
Section: Discussionsupporting
confidence: 82%
“…Dudley and colleagues (Dudley et al, 1982) reported that a 60mg/kg single dose of α-chloralose reduces the cerebral glucose utilization rate to 35−47% of that in the awake preparation in the cortex, and Nakao et al (2001) found thata 50mg/kg bolus followed by a 40 mg/kg/h maintenance dose reduced glucose utilization to 36% in the sensory motor cortex. These reductions in cerebral glucose metabolism in the cortex are very similar to the reductions observed with isoflurane at the concentrations used in the present study (Krafft et al, 2000;Ori et al, 1986). In addition, the α-chloralose dosing used (60 mg/kg bolus; 30 mg/kg/hr maintenance) is in line with the average dosing used in a variety of functional activation studies (64±15 mg/kg; 34±10 mg/kg/hr).…”
Section: Discussionsupporting
confidence: 82%
“…3) Table 3. Local cerebral blood flow of the experimental groups (with permission from [16,17] between local CBF and local cerebral glucose utilization was preserved but was shifted to a higher level (Fig. 3) (P < 0.05).…”
Section: Coupling Of Blood Flow To Metabolismmentioning
confidence: 96%
“…Table 1. Physiological variables of the experimental groups (with permission from [16,17] [16,17] [16,17]). …”
Section: Cerebral Glucose Utilization (Or Brain Metabolism)mentioning
confidence: 99%
See 2 more Smart Citations